Small Farm Food Safety, Fresh Produce—Part 2: The Buck Stops Here - Amy Simonne; Mickie E. Swisher; K. N. Moore; Kaylene Sattanno (EDIS)
Small Farm Food Safety, Fresh Produce is a short, interactive training program that introduces food-safety concepts as applied to fresh produce. The concepts are based on the FDA’s Guide to Minimized Microbial Food Safety Hazards for Fresh Fruits and Vegetables (FDA-GAPs). Part 2 consists of a group discussion based on four scenarios in which people obtained food poisoning. Participants will try to identify possible points of contamination in the production and distribution of the food. This 5-page fact sheet is a minor revision written by Amy Simonne, M. E. Swisher, K. N. Moore, and Kaylene Sattanno, and published by the Department of Family, Youth and Community Sciences, July 2017.